2016
DOI: 10.1037/a0039490
|View full text |Cite
|
Sign up to set email alerts
|

Are traits useful? Explaining trait manifestations as tools in the pursuit of goals.

Abstract: Traits and motivation mainly have been treated separately for almost a century. The purpose of these studies is to test the proposal that traits and motivation are intricately linked. Specifically, that one explanation for traits, at least in terms of their descriptiveness of what people actually do, is the goals people pursue. Study 1 used experience-sampling methodology to show that almost half the variance in extraversion and conscientiousness manifestation was explained by goal pursuit differences. Both wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
131
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(148 citation statements)
references
References 56 publications
14
131
3
Order By: Relevance
“…These results speak to the capacity for structural dimensions of goals to energize and direct behavior (Austin & Vancouver, 1996), and they provide more support for the recent hypothesis that Big Five behaviors are enacted in the service of goal achievement (McCabe & Fleeson, 2012; 2016). The results also might raise the possibility that the within-person, state level covariation of approach/avoidance goals and extraverted/neurotic states is one explanation for the between-person associations between these constructs (Elliot & Thrash, 2002).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…These results speak to the capacity for structural dimensions of goals to energize and direct behavior (Austin & Vancouver, 1996), and they provide more support for the recent hypothesis that Big Five behaviors are enacted in the service of goal achievement (McCabe & Fleeson, 2012; 2016). The results also might raise the possibility that the within-person, state level covariation of approach/avoidance goals and extraverted/neurotic states is one explanation for the between-person associations between these constructs (Elliot & Thrash, 2002).…”
Section: Discussionsupporting
confidence: 53%
“…This characterization is in line with results from an experience sampling study that examined the links among these variables at the state level (Heller et al, 2007). Further, more recent research has suggested that personality states are enacted in the service of meeting one's goals (McCabe & Fleeson, 2012; 2016). Thus, we sought to extend our mediation model to include the approach/avoidance goal construct as an antecedent to personality states.…”
Section: A Self-regulation Perspective On Behavior Goals Velocity Amentioning
confidence: 99%
“…From a theoretical standpoint, personality theories argue that self-reported traits do not merely represent the aggregation of moments or states (e.g., Augustine & Larsen, 2012;McCabe & Fleeson, 2016), in that people rely on different types of information when reporting on states rather than traits (Robinson & Clore, 2002). In keeping with this, meaningful differences between trait and state rumination have been reported.…”
mentioning
confidence: 60%
“…Given that individuals differ in what is important to them (Roccas, Sagiv, Schwartz, & Knafo, ), it is unlikely that people all value and pursue the same emotion regulation goals. Indeed, while goals can shift across situations (McCabe & Fleeson, ), there are still stable individual differences in goals (e.g., Reisz, Boudreaux, & Ozer, ; Roberts & Robins, ). Individual differences in emotion regulation goals are important to consider because goals impact how people typically behave (Austin & Vancouver, ) and have downstream consequences for well‐being if pursued chronically (e.g., Brunstein, Schultheiss, & Grassmann, ).…”
Section: Introductionmentioning
confidence: 99%